ORTA ÁSIRLER TÚRKIY ÁDEBIYATÍNDA ShEShENLIK DÁSTÚRLER - Orazov, Á.O. (SCIENCE and SOCIETY, 2025)
This article analyzes the historical foundations and artistic characteristics of oratory that developed in Turkic literature between the 11th and 14th centuries. Rhetorical techniques, question-and-answer structures, proverbs, and aphorisms in the works of Yusuf Khass Hajib, Mahmud Kashgari, Ahmad Yugnaki, Khwarezmi, Sayfi Sarayi, and Qutb were examined. The role and spiritual-cultural significance of medieval written monuments in shaping the rhetorical tradition were elucidated. The article illuminates the function of oratory in transmitting folk wisdom and ethical values to future generations.
Keywords: Turkic literature; oratory; rhetoric; Yusuf Khas Hajib; Mahmud Kashgari; Middle Ages; aphorism; question and answer